Colored aluminum anodized film and method for producing the same

CN120818873BActive Publication Date: 2026-10-30SHENZHEN JINMING AVIATION TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510958976.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2026-10-30
Estimated Expiration
2045-07-11

AI Technical Summary

Technical Problem

但是该方法制备的着色铝阳极氧化膜的颜色稳定性以及耐候性偏差

Benefits of technology

本发明通过依次将铝片进行电化学抛光、阳极氧化,得到铝阳极氧化膜,然后将铝阳极氧化膜浸入特定的偶氮前驱体溶液中,利用重氮盐和磺酸苯之间的偶氮化反应,在多孔氧化膜的孔隙中原位合成红色偶氮染料,完成对铝氧化膜的着色。本发明通过合成磺酸改性阿仑膦酸,并将其和硫脲、硫酸复配形成电化学抛光液,可以有效提高铝片表面电化学抛光质量,降低铝片表面粗糙度,为后续形成均匀的氧化膜以及均匀牢固着色提供了良好的基础。此外,本发明通过合成同时具有磷酸基、羧基和醇氨基的电解液添加剂,并将该添加剂与乳酸复配,可以形成具有较好表面质量以及孔隙尺寸合适的多孔氧化膜,为后续原位合成的偶氮染料在孔隙中固定负载提供良好基础。最后,本发明通过筛选特定结构的偶氮前驱体,可以使偶氮分子与多孔膜的孔隙尺寸良好匹配,并利用偶氮分子上的磺酸基进一步提高偶氮染料在多孔膜上的负载固定,进而得到具有良好着色效果的铝氧化膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818873B_ABST
    Figure CN120818873B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of aluminum alloy materials, and particularly relates to a colored aluminum anodic oxide film and a preparation method thereof. The application obtains the aluminum anodic oxide film by sequentially performing electrochemical polishing and anodic oxidation on aluminum, then immerses the aluminum anodic oxide film into an azo precursor solution, utilizes the azo reaction between the diazonium salt and the sulfonic acid benzene to in-situ synthesize red azo dye in the pores of the porous oxide film, and completes the coloring of the aluminum oxide film. The application can effectively improve the electrochemical polishing quality of the aluminum sheet surface by synthesizing sulfonic acid modified alendronate and compounding to form the electrochemical polishing solution. The application uses the electrolyte additive with phosphoric acid group, carboxyl group and alcohol amino group for anodic oxidation to form the porous oxide film with suitable pore size, finally screens the azo precursor with specific structure, and utilizes the sulfonic acid group on the azo molecule to further improve the loading and fixation of the azo dye on the porous film, so that the aluminum oxide film with good coloring effect is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aluminum alloy material technology, specifically a colored aluminum anodic oxide film and its preparation method. Background Technology

[0002] Aluminum is a lightweight metal with advantages such as light weight, corrosion resistance, good ductility, and ease of processing and shaping, making it widely used in packaging, construction, and arts and crafts. In dry air, a dense oxide film of a certain thickness forms on the surface of aluminum, preventing further oxidation. However, this natural oxide film does not meet the requirements for aluminum's protective properties. Therefore, to further improve the surface properties of aluminum, surface treatment is usually necessary. Aluminum and its alloys undergo anodizing in an electrolyte, forming a porous oxide film on the surface, known as aluminum anolyte (AAO) film. This film has good corrosion resistance and wear resistance. Chemical dyeing or secondary electrolytic coloring can yield AAO colored film layers with protective and decorative effects.

[0003] There are many methods for coloring aluminum anodic oxide films, but currently, organic immersion coloring and inorganic salt electrolytic coloring are widely used. Organic immersion coloring involves immersing the aluminum anodic oxide film in a dye or dye precursor solution. The dye molecules are deposited and fixed in the pores of the aluminum anodic oxide film through physical and chemical reactions, thereby obtaining a colored aluminum anodic oxide film with rich and bright colors. However, the color stability and weather resistance of the colored aluminum anodic oxide films prepared by this method are poor. Summary of the Invention

[0004] To address the above problems, this invention provides a colored aluminum anodic oxide film and its preparation method, which solves the problems of color stability and weather resistance deviation in current colored aluminum anodic oxide films.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a colored aluminum anodic oxide film includes the following steps: aluminum sheets are degreased and oxide scale removed, then electrochemically polished to obtain a pretreated aluminum sheet; the pretreated aluminum sheet is then anodized to form an aluminum anodic oxide film on the surface of the aluminum sheet; finally, the aluminum anodic oxide film is sequentially immersed in a diazonium salt solution and a mixed solution to obtain the colored aluminum anodic oxide film; the electrolytic polishing solution used in the electrochemical polishing is composed of water, thiourea, sulfonic acid-modified alendronic acid, and sulfuric acid; the electrolyte used in the anodizing process is composed of water, lactic acid, electrolyte additives, and aluminum sulfate; the diazonium salt is 2-amino-5-ethylpyrazine diazonium salt; and the mixed solution contains terephthalic acid; the chemical structure of the sulfonic acid-modified alendronic acid is shown below: The chemical structure of the electrolyte additive is shown below: Preferably, in the electropolishing solution, the mass fraction of thiourea is 1-3%, the mass fraction of sulfonic acid-modified alendronic acid is 15-30%, and the mass fraction of sulfuric acid is 10-20%.

[0006] Preferably, during the electrochemical polishing process, the temperature of the electrolytic polishing solution is controlled at 35~45℃, and the current density is 0.3~0.5A / cm². 2 The electrochemical polishing time is 4-7 minutes.

[0007] Preferably, the preparation method of the sulfonic acid modified alendronic acid is as follows: (4-amino-1-hydroxybutylene)bisphosphonate and 4-(chlorosulfonyl)benzoyl chloride are mixed and reacted, and then mixed and reacted with water to obtain sulfonic acid modified alendronic acid; the molar ratio of (4-amino-1-hydroxybutylene)bisphosphonate and 4-(chlorosulfonyl)benzoyl chloride is 1:1.05~1.1.

[0008] Preferably, in the electrolyte used for anodizing, the concentration of lactic acid is 70-90 g / L, the concentration of electrolyte additives is 40-60 g / L, and the concentration of aluminum sulfate is 15-25 g / L.

[0009] Preferably, during anodizing, the electrolyte temperature is 25~35℃ and the current density is 3~5A / dm³. 2 The time is 45-60 minutes.

[0010] Preferably, the electrolyte additive is prepared as follows: allyl phosphoric acid and diisopropanolamine are mixed and reacted at 60-75°C for 8-10 hours to obtain an intermediate; then the intermediate and bromocarboxylic acid are mixed and reacted at 70-75°C for 3-5 hours to obtain the electrolyte additive; the molar ratio of allyl phosphoric acid, diisopropanolamine and bromocarboxylic acid is 1.1-1.2:1:2-3; the bromocarboxylic acid is bromosuccinic acid.

[0011] Preferably, the diazonium salt solution is prepared as follows: 2-amino-5-ethylpyrazine, hydrochloric acid, and sodium nitrite aqueous solution are mixed and reacted at 0~5℃ to obtain the diazonium salt solution; the mass ratio of 2-amino-5-ethylpyrazine to hydrochloric acid is 1:2~2.5, the mass fraction of hydrochloric acid is 16~18%, and the molar ratio of 2-amino-5-ethylpyrazine to sodium nitrite is 1:1.1~1.3.

[0012] Preferably, the mixed solution is prepared as follows: terephthalic acid, N,N-dimethylformamide and sodium carbonate are mixed to obtain a mixed solution; the molar ratio of terephthalic acid and sodium carbonate is 1:3~4, and the mass ratio of terephthalic acid and N,N-dimethylformamide is 1:5~7.

[0013] A colored aluminum anodic oxide film prepared by the method described above.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention involves sequentially electrochemically polishing and anodizing aluminum sheets to obtain an aluminum anodic oxide film. The aluminum anodic oxide film is then immersed in a specific azo precursor solution. Utilizing the azo reaction between diazonium salt and sulfonic acid benzene, a red azo dye is synthesized in situ within the pores of the porous oxide film, thus coloring the aluminum oxide film. This invention also utilizes the synthesis of sulfonic acid-modified alendronic acid, which, when combined with thiourea and sulfuric acid to form an electrochemical polishing solution, effectively improves the electrochemical polishing quality of the aluminum sheet surface, reduces surface roughness, and provides a good foundation for the subsequent formation of a uniform oxide film and uniform, firm coloring. Furthermore, this invention synthesizes an electrolyte additive containing phosphate, carboxyl, and amino groups, and combines this additive with lactic acid to form a porous oxide film with good surface quality and suitable pore size, providing a good foundation for the subsequent in-situ synthesis of the azo dye and its fixation within the pores. Finally, by screening azo precursors with specific structures, this invention can achieve a good match between the pore size of azo molecules and porous membranes, and further improve the loading and fixation of azo dyes on porous membranes by utilizing the sulfonic acid groups on azo molecules, thereby obtaining aluminum oxide films with good coloring effects. Attached Figure Description

[0015] Figure 1 The above is the 1H NMR spectrum of the sulfonic acid-modified alendronic acid prepared in Example 1 of this invention; Figure 2 The image shows the 1H NMR spectrum of the electrolyte additive prepared in Example 1 of this invention. Detailed Implementation

[0016] To enable those skilled in the art to better understand the technical solution, the present invention will be described in detail below with reference to embodiments. The description in this part is only exemplary and explanatory, and should not be used to limit the scope of protection of the present invention in any way.

[0017] Example 1

[0018] The method for preparing the colored aluminum anodic oxide film in this embodiment includes the following steps: (1) The aluminum sheet is washed and degreased with a degreasing agent to obtain degreased aluminum sheet; the degreasing agent is composed of water, sodium dodecyl sulfate and potassium phosphate, the concentration of sodium dodecyl sulfate is 8 g / L and the concentration of potassium phosphate is 50 g / L.

[0019] (2) Immerse the degreased aluminum sheet in a sodium hydroxide solution (mass fraction of 35%) at a temperature of 50°C. After 2 minutes, remove the sheet and rinse it with water until the pH of the washing solution is neutral to obtain the aluminum sheet after removing the oxide scale.

[0020] (3) The aluminum sheet after oxide removal is electrochemically polished to obtain a pretreated aluminum sheet; the electrolytic polishing solution during electrochemical polishing consists of water, thiourea, sulfonic acid-modified alendronic acid, and sulfuric acid, with a mass fraction of 1% for thiourea, 15% for sulfonic acid-modified alendronic acid, and 10% for sulfuric acid; during the electrochemical polishing process, the temperature of the electrolytic polishing solution is controlled at 35℃ and the current density is 0.3A / cm. 2 The electrochemical polishing time was 4 min. The preparation method of sulfonic acid-modified alendronate is as follows: (4-amino-1-hydroxybutylene)bisphosphonic acid and dichloromethane were added to a stirred tank and stirred until homogeneous to obtain a 5% (mass fraction) solution of (4-amino-1-hydroxybutylene)bisphosphonic acid; 4-(chlorosulfonyl)benzoyl chloride and dichloromethane were added to a stirred tank and stirred until homogeneous to obtain a 15% (mass fraction) solution of 4-(chlorosulfonyl)benzoyl chloride; the temperature of the (4-amino-1-hydroxybutylene)bisphosphonic acid solution was adjusted to 0℃, and under stirring conditions, the 4-(chlorosulfonyl)benzoyl chloride solution was added dropwise to the (4-amino-1-hydroxybutylene)bisphosphonic acid solution. After the addition was complete, triethylamine was added to the reaction system, and the mixture was adjusted to room temperature. The reaction was continued with stirring for 5 hours. The mixture was then filtered, and the filtrate was distilled under reduced pressure to remove the solvent, yielding a concentrate. The concentrate was added to water (the mass of water was 1.2 times the mass of the concentrate), and the mixture was stirred for 8 hours. The water was removed by distillation under reduced pressure again, yielding a crude product. Finally, the crude product was purified by column chromatography (the eluent consisted of petroleum ether, methanol, and chloroform in a volume ratio of 8:2:1) to obtain sulfonic acid-modified alendronic acid. The molar ratio of (4-amino-1-hydroxybutylene)bisphosphonate, 4-(chlorosulfonyl)benzoyl chloride, and triethylamine was 1:1.05:1.3. The 1H NMR spectrum of sulfonic acid-modified alendronic acid is shown below. Figure 1 As shown, the chemical structure is as follows:

[0021] (4) The pretreated aluminum sheet is anodized to form an aluminum anodized film on the surface of the aluminum sheet; the electrolyte used in the anodizing process consists of water, lactic acid, electrolyte additives and aluminum sulfate, with a lactic acid concentration of 70 g / L, an electrolyte additive concentration of 40 g / L and an aluminum sulfate concentration of 15 g / L; during the anodizing process, the electrolyte temperature is 25℃ and the current density is 3 A / dm³. 2 The time is 45 minutes; The preparation method of the electrolyte additive is as follows: allyl phosphoric acid and acetonitrile are added to a stirred tank and stirred evenly to obtain an allyl phosphoric acid solution with a mass fraction of 18%. Then, diisopropanolamine is added to the stirred tank, and the stirred tank is heated so that the material in the stirred tank is stirred and reacted at 60°C for 8 hours. After cooling to room temperature, the liquid after reaction is distilled under reduced pressure to remove the solvent and obtain the intermediate.

[0022] Then, the intermediate, bromocarboxylic acid, and acetonitrile (acetonitrile mass being 80% of the intermediate mass) were added to a stirred tank and stirred until homogeneous. The mixture was then heated to 80°C and refluxed for 5 hours. The resulting system was then distilled under reduced pressure to remove the acetonitrile, yielding a concentrate. This concentrate was then purified by column chromatography to obtain the electrolyte additive. The molar ratio of allyl phosphate, diisopropanolamine, and bromocarboxylic acid was 1.1:1:2, and the bromocarboxylic acid was bromosuccinic acid. The eluent for column chromatography consisted of petroleum ether, methanol, and dichloromethane in a volume ratio. The 1H NMR spectrum of the electrolyte additive is shown below. Figure 2 As shown, the chemical structure is as follows:

[0023] (5) Add 2-amino-5-ethylpyrazine and hydrochloric acid to a stirred reactor, adjust the temperature of the material in the stirred reactor to 0°C, then add sodium nitrite aqueous solution (mass fraction of 20%), stir and react for 3 hours to obtain a diazonium salt solution; wherein, the mass ratio of 2-amino-5-ethylpyrazine to hydrochloric acid is 1:2, the mass fraction of hydrochloric acid is 16%, and the molar ratio of 2-amino-5-ethylpyrazine to sodium nitrite is 1:1.1.

[0024] Terephthalic acid, N,N-dimethylformamide, and sodium carbonate were added to a reaction vessel and stirred until the solid was fully dissolved to obtain a mixed solution; wherein the molar ratio of terephthalic acid to sodium carbonate was 1:3, and the mass ratio of terephthalic acid to N,N-dimethylformamide was 1:5.

[0025] (6) Immerse the aluminum sheet with an aluminum anodic oxide film on its surface prepared in step (4) into the mixed solution prepared in step (5), and ultrasonically disperse it for 5 min. After taking it out, immerse it in the diazonium salt solution prepared in step (5) for 8 min. After taking it out, wash the aluminum sheet with deionized water and dry it to form a red colored oxide film on the surface of the aluminum sheet.

[0026] Example 2

[0027] The method for preparing the colored aluminum anodic oxide film in this embodiment includes the following steps: (1) The aluminum sheet is washed and degreased with a degreasing agent to obtain degreased aluminum sheet; the degreasing agent is composed of water, sodium dodecyl sulfate and potassium phosphate, the concentration of sodium dodecyl sulfate is 9 g / L and the concentration of potassium phosphate is 55 g / L.

[0028] (2) Immerse the degreased aluminum sheet in a sodium hydroxide solution (mass fraction of 40%) at a temperature of 55°C. After 2 minutes, remove the sheet and rinse it with water until the pH of the washing solution is neutral to obtain the aluminum sheet after removing the oxide scale.

[0029] (3) The aluminum sheet after oxide removal is electrochemically polished to obtain a pretreated aluminum sheet; the electrolytic polishing solution during electrochemical polishing consists of water, thiourea, sulfonic acid-modified alendronic acid, and sulfuric acid, with a mass fraction of 2% for thiourea, 19% for sulfonic acid-modified alendronic acid, and 15% for sulfuric acid; during the electrochemical polishing process, the temperature of the electrolytic polishing solution is controlled at 40℃ and the current density is 0.4A / cm. 2 The electrochemical polishing time was 6 min. The preparation method of sulfonic acid-modified alendronate is as follows: (4-amino-1-hydroxybutylene)bisphosphonic acid and dichloromethane were added to a stirred tank and stirred until homogeneous to obtain a 6% (mass fraction) solution of (4-amino-1-hydroxybutylene)bisphosphonic acid; 4-(chlorosulfonyl)benzoyl chloride and dichloromethane were added to a stirred tank and stirred until homogeneous to obtain an 18% (mass fraction) solution of 4-(chlorosulfonyl)benzoyl chloride; the temperature of the (4-amino-1-hydroxybutylene)bisphosphonic acid solution was adjusted to 2℃, and under stirring conditions, the 4-(chlorosulfonyl)benzoyl chloride solution was added dropwise to the (4-amino-1-hydroxybutylene)bisphosphonic acid solution. After the addition was complete, triethylamine was added to the reaction system, and the mixture was adjusted to room temperature. The reaction was continued with stirring for 6 hours. The mixture was filtered, and the filtrate was distilled under reduced pressure to remove the solvent, yielding a concentrate. The concentrate was added to water (the mass of water was 1.3 times the mass of the concentrate), and the mixture was stirred for 9 hours. The water was removed by distillation under reduced pressure again, yielding a crude product. Finally, the crude product was purified by column chromatography (the eluent consisted of petroleum ether, methanol, and chloroform in a volume ratio of 8:2:1) to obtain sulfonic acid-modified alendronic acid. The molar ratio of (4-amino-1-hydroxybutylene)bisphosphonate, 4-(chlorosulfonyl)benzoyl chloride, and triethylamine was 1:1.08:1.4. The chemical structure of sulfonic acid-modified alendronic acid is shown below:

[0030] (4) The pretreated aluminum sheet is anodized to form an aluminum anodized film on the surface of the aluminum sheet; the electrolyte used in the anodizing process consists of water, lactic acid, electrolyte additives and aluminum sulfate, with a lactic acid concentration of 80 g / L, an electrolyte additive concentration of 50 g / L and an aluminum sulfate concentration of 20 g / L; during the anodizing process, the electrolyte temperature is 30℃ and the current density is 4 A / dm³. 2 The time is 50 minutes; The preparation method of the electrolyte additive is as follows: allyl phosphoric acid and acetonitrile are added to a stirred tank and stirred evenly to obtain an allyl phosphoric acid solution with a mass fraction of 20%. Then, diisopropanolamine is added to the stirred tank, and the stirred tank is heated so that the material in the stirred tank is stirred and reacted at 70°C for 9 hours. After cooling to room temperature, the liquid after reaction is distilled under reduced pressure to remove the solvent and obtain the intermediate.

[0031] Then, the intermediate, bromocarboxylic acid, and acetonitrile (acetonitrile mass equal to 100% of the intermediate mass) were added to a stirred tank and stirred until homogeneous. The mixture was then heated to 80°C and refluxed for 5 hours. The resulting system was then distilled under reduced pressure to remove the acetonitrile, yielding a concentrate. Finally, the concentrate was purified by column chromatography to obtain the electrolyte additive. The molar ratio of allyl phosphoric acid, diisopropanolamine, and bromocarboxylic acid was 1.1:1:3, and the bromocarboxylic acid was bromosuccinic acid. The eluent for column chromatography consisted of petroleum ether, methanol, and dichloromethane in a volume ratio. The chemical structure of the electrolyte additive is shown below:

[0032] (5) Add 2-amino-5-ethylpyrazine and hydrochloric acid to a stirred reactor, adjust the temperature of the material in the stirred reactor to 2°C, then add sodium nitrite aqueous solution (mass fraction of 22%), stir and react for 3 hours to obtain a diazonium salt solution; wherein, the mass ratio of 2-amino-5-ethylpyrazine to hydrochloric acid is 1:2.2, the mass fraction of hydrochloric acid is 17%, and the molar ratio of 2-amino-5-ethylpyrazine to sodium nitrite is 1:1.2.

[0033] Terephthalic acid, N,N-dimethylformamide, and sodium carbonate were added to a reaction vessel and stirred until the solid was fully dissolved to obtain a mixed solution. The molar ratio of terephthalic acid to sodium carbonate was 1:3, and the mass ratio of terephthalic acid to N,N-dimethylformamide was 1:6.

[0034] (6) Immerse the aluminum sheet with an aluminum anodic oxide film on its surface prepared in step (4) into the mixed solution prepared in step (5), and ultrasonically disperse it for 6 min. After taking it out, immerse it in the diazonium salt solution prepared in step (5) for 9 min. After taking it out, wash the aluminum sheet with deionized water and dry it to form a red colored oxide film on the surface of the aluminum sheet.

[0035] Example 3

[0036] The method for preparing the colored aluminum anodic oxide film in this embodiment includes the following steps: (1) The aluminum sheet is washed and degreased with a degreasing agent to obtain degreased aluminum sheet; the degreasing agent is composed of water, sodium dodecyl sulfate and potassium phosphate, the concentration of sodium dodecyl sulfate is 10 g / L and the concentration of potassium phosphate is 60 g / L.

[0037] (2) Immerse the degreased aluminum sheet in a sodium hydroxide solution (mass fraction of 45%) at a temperature of 60°C. After 3 minutes, take it out and rinse it with water until the pH of the washing solution is neutral to obtain the aluminum sheet after removing the oxide scale.

[0038] (3) The aluminum sheet after oxide removal is electrochemically polished to obtain a pretreated aluminum sheet; the electrolytic polishing solution during electrochemical polishing consists of water, thiourea, sulfonic acid-modified alendronic acid, and sulfuric acid, with a mass fraction of 3% for thiourea, 30% for sulfonic acid-modified alendronic acid, and 20% for sulfuric acid; during the electrochemical polishing process, the temperature of the electrolytic polishing solution is controlled at 45℃ and the current density is 0.5A / cm. 2 The electrochemical polishing time was 7 min. The preparation method of sulfonic acid-modified alendronate is as follows: (4-amino-1-hydroxybutylene)bisphosphonic acid and dichloromethane were added to a stirred tank and stirred until homogeneous to obtain an 8% (mass fraction) solution of (4-amino-1-hydroxybutylene)bisphosphonic acid; 4-(chlorosulfonyl)benzoyl chloride and dichloromethane were added to a stirred tank and stirred until homogeneous to obtain a 20% (mass fraction) solution of 4-(chlorosulfonyl)benzoyl chloride; the temperature of the (4-amino-1-hydroxybutylene)bisphosphonic acid solution was adjusted to 5℃, and under stirring conditions, the 4-(chlorosulfonyl)benzoyl chloride solution was added dropwise to the (4-amino-1-hydroxybutylene)bisphosphonic acid solution. After the addition was complete, triethylamine was added to the reaction system, and the mixture was adjusted to room temperature. The reaction was continued with stirring for 7 hours. The mixture was then filtered, and the filtrate was distilled under reduced pressure to remove the solvent, yielding a concentrate. The concentrate was added to water (the mass of water was 1.5 times the mass of the concentrate), and the mixture was stirred for 10 hours. The water was removed by distillation under reduced pressure again to obtain a crude product. Finally, the crude product was purified by column chromatography (the eluent consisted of petroleum ether, methanol, and chloroform in a volume ratio of 8:2:1) to obtain sulfonic acid-modified alendronic acid. The molar ratio of (4-amino-1-hydroxybutylene)bisphosphonate, 4-(chlorosulfonyl)benzoyl chloride, and triethylamine was 1:1.1:1.5. The chemical structure of sulfonic acid-modified alendronic acid is shown below:

[0039] (4) The pretreated aluminum sheet is anodized to form an aluminum anodized film on the surface of the aluminum sheet; the electrolyte used in the anodizing process consists of water, lactic acid, electrolyte additives and aluminum sulfate, with a lactic acid concentration of 90 g / L, an electrolyte additive concentration of 60 g / L and an aluminum sulfate concentration of 25 g / L; during the anodizing process, the electrolyte temperature is 35℃ and the current density is 5 A / dm³. 2 The time is 60 minutes; The preparation method of the electrolyte additive is as follows: allyl phosphoric acid and acetonitrile are added to a stirred tank and stirred evenly to obtain an allyl phosphoric acid solution with a mass fraction of 24%. Then, diisopropanolamine is added to the stirred tank, and the stirred tank is heated to allow the material in the stirred tank to react at 75°C for 10 hours. After cooling to room temperature, the liquid after reaction is distilled under reduced pressure to remove the solvent and obtain the intermediate.

[0040] Then, the intermediate, bromocarboxylic acid, and acetonitrile (acetonitrile mass being 120% of the intermediate mass) were added to a stirred tank and stirred until homogeneous. The mixture was then heated to 80°C and refluxed for 5 hours. The resulting system was then distilled under reduced pressure to remove the acetonitrile, yielding a concentrate. This concentrate was then purified by column chromatography to obtain the electrolyte additive. The molar ratio of allyl phosphate, diisopropanolamine, and bromocarboxylic acid was 1.2:1:3, and the bromocarboxylic acid was bromosuccinic acid. The eluent for column chromatography consisted of petroleum ether, methanol, and dichloromethane in a volume ratio. The chemical structure of the electrolyte additive is shown below:

[0041] (5) Add 2-amino-5-ethylpyrazine and hydrochloric acid to a stirred reactor, adjust the temperature of the material in the stirred reactor to 5°C, then add sodium nitrite aqueous solution (mass fraction of 25%), stir and react for 4 hours to obtain a diazonium salt solution; wherein, the mass ratio of 2-amino-5-ethylpyrazine to hydrochloric acid is 1:2.5, the mass fraction of hydrochloric acid is 18%, and the molar ratio of 2-amino-5-ethylpyrazine to sodium nitrite is 1:1.3.

[0042] Terephthalic acid, N,N-dimethylformamide, and sodium carbonate were added to a reaction vessel and stirred until the solid was fully dissolved to obtain a mixed solution; wherein the molar ratio of terephthalic acid to sodium carbonate was 1:4, and the mass ratio of terephthalic acid to N,N-dimethylformamide was 1:7.

[0043] (6) Immerse the aluminum sheet with an aluminum anodic oxide film on its surface prepared in step (4) into the mixed solution prepared in step (5), and ultrasonically disperse it for 8 min. After taking it out, immerse it in the diazonium salt solution prepared in step (5) for 10 min. After taking it out, wash the aluminum sheet with deionized water and dry it to form a red colored oxide film on the surface of the aluminum sheet.

[0044] Comparative Example 1 The difference between the preparation method of the colored aluminum anodic oxide film in this comparative example and the preparation method of the colored aluminum anodic oxide film in Example 1 is that in step (3) of the preparation method of the colored aluminum anodic oxide film in this comparative example, the sulfonic acid modified alendronic acid is replaced with benzenesulfonic acid and (4-amino-1-hydroxybutylene) bisphosphonic acid in a molar ratio of 1:1.

[0045] Comparative Example 2 The difference between the preparation method of the colored aluminum anodic oxide film in this comparative example and the preparation method of the colored aluminum anodic oxide film in Example 1 is that in step (3) of the preparation method of the colored aluminum anodic oxide film in this comparative example, sulfuric acid is replaced with nitric acid.

[0046] Comparative Example 3 The difference between the preparation method of the colored aluminum anodic oxide film in this comparative example and the preparation method of the colored aluminum anodic oxide film in Example 1 is that thiourea is replaced with urea in step (3) of the preparation method of the colored aluminum anodic oxide film in this comparative example.

[0047] Comparative Example 4 The difference between the preparation method of the colored aluminum anodic oxide film in this comparative example and the preparation method of the colored aluminum anodic oxide film in Example 1 is that diisopropanolamine is replaced with diethanolamine in the preparation method of electrolyte additive in step (4) of the preparation method of the colored aluminum anodic oxide film in this comparative example.

[0048] Comparative Example 5 The difference between the preparation method of the colored aluminum anodic oxide film in this comparative example and the preparation method of the colored aluminum anodic oxide film in Example 1 is that the bromocarboxylic acid in the preparation method of the electrolyte additive in step (4) of the preparation method of the colored aluminum anodic oxide film in this comparative example is bromomalonic acid.

[0049] Comparative Example 6 The difference between the preparation method of the colored aluminum anodic oxide film in this comparative example and the preparation method of the colored aluminum anodic oxide film in Example 1 is that the bromocarboxylic acid in the preparation method of the electrolyte additive in step (4) of the preparation method of the colored aluminum anodic oxide film in this comparative example is 2-bromobutyric acid.

[0050] Comparative Example 7 The difference between the preparation method of the colored aluminum anodic oxide film in this comparative example and the preparation method of the colored aluminum anodic oxide film in Example 1 is that in step (4) of the preparation method of the colored aluminum anodic oxide film in this comparative example, the electrolyte additive is replaced with allyl phosphoric acid, diisopropanolamine and bromosuccinic acid in a molar ratio of 1:1:1.

[0051] Comparative Example 8 The difference between the preparation method of the colored aluminum anodic oxide film in this comparative example and the preparation method of the colored aluminum anodic oxide film in Example 1 is that in step (5) of the preparation method of the colored aluminum anodic oxide film in this comparative example, 2-amino-5-ethylpyrazine is replaced with 2-amino-5-methylpyrazine.

[0052] Comparative Example 9 The difference between the preparation method of the colored aluminum anodic oxide film in this comparative example and the preparation method of the colored aluminum anodic oxide film in Example 1 is that 2-amino-5-ethylpyrazine is replaced with aminopyrazine in step (5) of the preparation method of the colored aluminum anodic oxide film in this comparative example.

[0053] Comparative Example 10 The difference between the preparation method of the colored aluminum anodic oxide film in this comparative example and the preparation method of the colored aluminum anodic oxide film in Example 1 is that in step (5) of the preparation method of the colored aluminum anodic oxide film in this comparative example, terephthalic acid is replaced with isophthalic acid.

[0054] Comparative Example 11 The difference between the preparation method of the colored aluminum anodic oxide film in this comparative example and the preparation method of the colored aluminum anodic oxide film in Example 1 is that in step (5) of the preparation method of the colored aluminum anodic oxide film in this comparative example, terephthalic acid is replaced with benzenesulfonic acid.

[0055] Experimental Example To examine the electrochemical polishing effect of the electrolytic polishing solutions used in the various embodiments and comparative examples 1-3, the surface roughness of the pretreated aluminum sheets prepared in each embodiment and comparative examples 1-3 was tested, and the surface appearance characteristics of the pretreated aluminum sheets were observed with a magnifying glass. The test results are shown in Table 1. During the test, five test points at the same location were selected for each sample, and the average value of the test results at the five test points was taken as the final test result.

[0056] Table 1. Surface roughness and appearance of the pretreated aluminum sheets prepared in each embodiment and Comparative Examples 1-3

[0057] As shown in Table 1, the electropolishing solutions used in Examples 1-3 of this invention have better electropolishing effects than those in Comparative Examples 1-3. The pretreated aluminum sheets prepared have lower surface roughness, providing a good foundation for the subsequent formation of a uniform oxide film and uniform and firm coloring. According to the experimental results in Table 1, the sulfuric acid, sulfonic acid-modified alendronic acid, and thiourea in the electropolishing solution have a good compounding effect; the simultaneous use of all three can significantly improve the surface quality of the aluminum sheets.

[0058] Example of effect To examine the comprehensive performance of the colored oxide films prepared in each embodiment and comparative example, the coloring effect of the colored oxide films in each embodiment and comparative example was evaluated. The color of the colored oxide films in each embodiment and comparative example was observed and recorded. The color uniformity, salt spray resistance, and weather resistance of the colored oxide films in each embodiment and comparative example were also tested. The results are shown in Table 2. The color uniformity test method is as follows: Ten identical test points were selected for each sample. The color difference ΔE between any two test points on each sample was measured using a colorimeter. The maximum color difference was recorded as the color uniformity test result for that sample. The salt spray resistance test method is as follows: The test sample was placed in a test chamber, and a salt solution containing 5% sodium chloride and a pH of 7 was sprayed through a spray device. The salt spray settled onto the test sample, and the time when corrosion spots appeared on the sample surface was observed and recorded. The time when corrosion spots appeared on the sample surface was taken as the salt spray resistance test result. The weather resistance test method is as follows: The test sample is placed in an artificial ultraviolet aging chamber to simulate the ultraviolet light exposure test under natural conditions. The color difference ΔE at the same position on the sample surface before the weather resistance test and after 3000 hours of testing is observed and recorded. The color difference ΔE is taken as the weather resistance test result. The comprehensive performance test results of the colored oxide films prepared in each embodiment and comparative example are shown in Table 2.

[0059] Table 2. Comprehensive performance test results of the colored oxide films prepared in each embodiment and comparative example.

[0060] Note: "-" indicates that it has not been tested.

[0061] As shown in Table 2, the colored aluminum anodic oxide film prepared by this invention exhibits a bright red color with good color uniformity at different locations. It also demonstrates good salt spray resistance and weather resistance, indicating promising application prospects. Furthermore, according to the test results in Table 1, the pretreated aluminum sheets prepared in Comparative Examples 1-4 have a large surface roughness and poor surface quality, leading to poor quality of the subsequent oxide film. This, in turn, affects the in-situ formation and fixation of azo dyes in the oxide film pores, resulting in poor final coloring effect.

[0062] As can be seen from Example 1 and Comparative Examples 5-6, when the bromocarboxylic acid is replaced by bromosuccinic acid or bromomalonic acid or 2-bromobutyric acid, the surface activity and acidity of the electrolyte additive are reduced due to the decrease in the number of carbon chains or carboxyl groups. This affects the formation quality of the oxide film and the pore size on the oxide film, resulting in a mismatch between the azo dye molecules and the pore size on the oxide film, leading to a poorer coloring effect.

[0063] As can be seen from Example 1 and Comparative Example 7, when the electrolyte additive is replaced with a mixture of allyl phosphoric acid, diisopropanolamine and bromosuccinic acid in a molar ratio of 1:1:1, although the electrolyte contains active groups such as carboxyl groups, sulfonic acid groups and alkanolamines, the change in the structure of the substance leads to a change in the anodic oxidation process, which in turn affects the formation of the final porous oxide film and the coloring effect of the azo dye.

[0064] As can be seen from Example 1 and Comparative Example 8, when 2-amino-5-ethylpyrazine is replaced with 2-amino-5-methylpyrazine, the side chain carbon chain length of the pyrazine amino compound is reduced, which makes it impossible for the azo molecules to be well embedded and fixed in the pores of the porous oxide film, thus affecting the coloring effect.

[0065] As can be seen from Example 1 and Comparative Example 10, after replacing terephthalic acid with isophthalic acid, the active sites of isophthalic acid are not unique, resulting in the synthesized azo dye having multiple structures, which affects the purity of the azo dye coloring product, and thus leads to poor color uniformity of the colored oxide film.

[0066] As can be seen from Example 1 and Comparative Examples 9 and 11, when 2-amino-5-ethylpyrazine is replaced with aminopyrazine or terephthalic acid is replaced with benzenesulfonic acid, the pyrazine amino compound lacks a side chain or the number of sulfonic acid groups in the synthesized azo molecule is too small. This results in a mismatch between the azo molecule and the pore structure of the porous oxide film or poor fixation of the azo molecule. Consequently, the azo molecule cannot be fixed and loaded in the pores of the porous oxide film, resulting in coloring failure.

[0067] It should be noted that, in this document, the terms "comprising," "including," and any other variations are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Specific examples have been used in this document to illustrate the principles and implementation methods of the present invention. These examples are merely for the purpose of helping to understand the method and core ideas of the present invention. The above descriptions are only preferred embodiments of the present invention. It should be pointed out that, due to the limitations of written expression and the objective existence of infinite specific structures, those skilled in the art can make several improvements, modifications, or variations without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner. These improvements, modifications, variations, or combinations, or the direct application of the concept and technical solution of the present invention to other situations without modification, should all be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a colored aluminum anodic oxide film, characterized in that, Includes the following steps: After degreasing and removing oxide scale, the aluminum sheet is electrochemically polished to obtain a pretreated aluminum sheet. Then, the pretreated aluminum sheet is anodized to form an aluminum anodized film on the surface of the aluminum sheet. Finally, the aluminum anodized film is immersed in a diazonium salt solution and a mixed solution in sequence to obtain a colored aluminum anodized film. The electropolishing solution used in the electrochemical polishing process consists of water, thiourea, sulfonic acid-modified alendronate, and sulfuric acid. The electrolyte used in the anodizing process consists of water, lactic acid, electrolyte additives, and aluminum sulfate. The diazonium salt is 2-amino-5-ethylpyrazine diazonium salt, and the mixture contains terephthalic acid. In the electropolishing solution, the mass fraction of thiourea is 1-3%, the mass fraction of sulfonic acid-modified alendronate is 15-30%, and the mass fraction of sulfuric acid is 10-20%. During the electrochemical polishing process, the temperature of the electropolishing solution is controlled at 35-45°C, and the current density is 0.3-0.5 A / cm². 2 The electrochemical polishing time is 4-7 minutes; in the electrolyte used for anodizing, the concentration of lactic acid is 70-90 g / L, the concentration of electrolyte additives is 40-60 g / L, and the concentration of aluminum sulfate is 15-25 g / L; during anodizing, the electrolyte temperature is 25-35℃, and the current density is 3-5 A / dm³. 2 The time is 45-60 min; the chemical structure of the sulfonic acid modified alendrolic acid is shown below: ; The chemical structure of the electrolyte additive is shown below: 。 2. The method for preparing a colored aluminum anodic oxide film according to claim 1, characterized in that, The preparation method of the sulfonic acid modified alendronic acid is as follows: (4-amino-1-hydroxybutylene)bisphosphonate and 4-(chlorosulfonyl)benzoyl chloride are mixed and reacted, and then mixed and reacted with water to obtain sulfonic acid modified alendronic acid; the molar ratio of (4-amino-1-hydroxybutylene)bisphosphonate and 4-(chlorosulfonyl)benzoyl chloride is 1:1.05~1.

1.

3. The method for preparing a colored aluminum anodic oxide film according to claim 1, characterized in that, The electrolyte additive is prepared as follows: allyl phosphoric acid and diisopropanolamine are mixed and reacted at 60-75°C for 8-10 h to obtain an intermediate. Then, the intermediate and bromocarboxylic acid are mixed and reacted at 70-75°C for 3-5 h to obtain the electrolyte additive. The molar ratio of allyl phosphoric acid, diisopropanolamine and bromocarboxylic acid is 1.1-1.2:1:2-3. The bromocarboxylic acid is bromosuccinic acid.

4. The method for preparing a colored aluminum anodic oxide film according to claim 1, characterized in that, The diazonium salt solution is prepared as follows: 2-amino-5-ethylpyrazine, hydrochloric acid, and sodium nitrite aqueous solution are mixed and reacted at 0~5℃ to obtain the diazonium salt solution; the mass ratio of 2-amino-5-ethylpyrazine to hydrochloric acid is 1:2~2.5, the mass fraction of hydrochloric acid is 16~18%, and the molar ratio of 2-amino-5-ethylpyrazine to sodium nitrite is 1:1.1~1.

3.

5. The method for preparing a colored aluminum anodic oxide film according to claim 1, characterized in that, The mixed solution is prepared as follows: terephthalic acid, N,N-dimethylformamide and sodium carbonate are mixed to obtain a mixed solution; the molar ratio of terephthalic acid and sodium carbonate is 1:3~4, and the mass ratio of terephthalic acid and N,N-dimethylformamide is 1:5~7.

6. A colored aluminum anodic oxide film prepared by the method described in any one of claims 1-5.

Citation Information

Patent Citations

  • Fireproof aging-resistant high-reflection aluminum-plastic composite film, preparation method thereof and application of fireproof aging-resistant high-reflection aluminum-plastic composite film in improvement of photovoltaic back power generation efficiency

    CN120191098A

  • Coloring method for aluminium anode oxidation film

    CN1587443A